The spirit in question [large type] - Kuhn, Cynthia G., 1965- (A Lila Maclean Academic Mystery, 2019)
"Cynthia Kuhn writes the Lila Maclean Academic Mystery Series: The Semester of Our Discontent, an Agatha Award recipient (Best First Novel); The Art of Vanishing, a Lefty Award nominee (Best Humorous Mystery); and The Spirit in Question. She is professor of English at MSU Denver, president of Sisters in Crime-Colorado, and member of Mystery Writers of America, International Thriller Writers, and Rocky Mountain Fiction Writers. For more information, please visit cynthiakuhn.net. This is part of "A Lila Maclean Academic Mystery" series."--